1992
DOI: 10.1007/bf02207082
|View full text |Cite
|
Sign up to set email alerts
|

Experimental animal models resembling rheumatoid arthritis

Abstract: The experimental animal models of arthritis which in certain aspects share similarities to human rheumatoid arthritis are reviewed. Various methods have been applied to induce in animals experimental models of arthritis which would provide important insights into the aetiopathogenetic mechanisms of human RA. Immunological methods and infectious agents induced the most interesting models. The histology of the synovial tissue, regardless of the inducing mechanisms, is similar to the lesions of RA. Yet, none of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…These data indicated that CIA mice display marked upregulation of IL-1b in joints accompanied by synovial growth similar to human RA. 1,2,4 Intramuscular gene therapy using IL-1Ra DNA inhibits CIA in mice As a plasmid expression vector for intramuscular gene therapy, we used pCK, which has been shown to drive a high level of gene expression in the skeletal and cardiac muscles of mice. 22,23 The human IL-1Ra coding sequence was cloned to pCK, resulting in pCK-IL-1Ra (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data indicated that CIA mice display marked upregulation of IL-1b in joints accompanied by synovial growth similar to human RA. 1,2,4 Intramuscular gene therapy using IL-1Ra DNA inhibits CIA in mice As a plasmid expression vector for intramuscular gene therapy, we used pCK, which has been shown to drive a high level of gene expression in the skeletal and cardiac muscles of mice. 22,23 The human IL-1Ra coding sequence was cloned to pCK, resulting in pCK-IL-1Ra (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…1 Although the causes of RA are not fully understood, various experimental and clinical studies suggest that proinflammatory cytokines, particularly interleukin-1 (IL-1) among others, have an important role in RA pathogenesis. [2][3][4][5] The IL-1 receptor antagonist (IL-1Ra) is a natural protein that competitively inhibits the binding of IL-1b and IL-1a to IL-1 receptor types I and II in humans and various animals, and improves the inflammatory symptoms of arthritis in experimental animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although the causes of RA are not fully understood, various experimental and clinical studies suggest that proinflammatory cytokines, particularly tumor necrosis factor-a (TNF-a), play an important role in RA pathogenesis. [2][3][4][5][6] TNF concentrations are increased in the synovial fluid of persons with active RA 7,8 and increased plasma levels of TNF are associated with joint pain.…”
Section: Introductionmentioning
confidence: 99%
“…Although CD90 + synovial fibroblasts are highly vulnerable to genetic modification, this cell population is also transient, with an apparent half-life in normal joints of less than 1 month (Gouze et al, 2007). This half-life decreases further in diseased joints (Remmers et al, 1990;Kaklamanis, 1992;Pan et al, 1999). If the majority of vector-transduced cells in a target joint are transient, the long-term therapeutic effects in the joint will be based on the small remaining nontransient cell population.…”
mentioning
confidence: 99%